Phosphoinositides: Two-Path Signaling in Neuronal Response to Oligomeric Amyloid β Peptide - Uranga, Romina Maria (2017)
We have previously demonstrated that oligomeric amyloid β peptide (oAβ) together with iron overload generates synaptic injury and activation of several signaling cascades. In this work, we characterized hippocampal neuronal response to oAβ. HT22 neurons exposed to 500 nM oAβ showed neither increased lipid peroxidation nor altered mitochondrial function. In addition, biophysical studies showed that oAβ did not perturb the lipid order of the membrane. Interestingly, although no neuronal damage could be demonstrated, oAβ was found to trigger bifurcated phosphoinositide-dependent signaling in the neuron, on one hand, the phosphorylation of insulin receptor, the phosphatidylinositol 3-kinase (PI3K)-dependent activation of Akt, its translocation to the nucleus and the concomitant phosphorylation, inactivation, and nuclear exclusion of the transcription factor Forkhead Box O3a (FoxO3a), and on the other, phosphoinositide-phospholipase C (PI-PLC)-dependent extracellular signal-regulated kinase 1/2 (ERK1/2) activation. Pharmacological manipulation of the signaling cascades was used in order to better characterize the role of oAβ-activated signals, and mitochondrial function was determined as a measure of neuronal viability. The inhibition of PI3K, PI-PLC, and general phosphoinositide metabolism impaired neuronal mitochondrial function. Furthermore, increased oAβ-induced cell death was observed in the presence of phosphoinositide metabolism inhibition. Our results allow us to conclude that oAβ triggers the activation of phosphoinositide-dependent signaling, which results in the subsequent activation of neuroprotective mechanisms that could be involved in the determination of neuronal fate.